Prevalence And Associated Factors Of Burnout At Bule Hora University In Southeast Ethiopia - Alemishet, Ayichluhim (Academic Journal of Psychology and Counseling, 2024)
The present study intended to assess the prevalence of burnout and its associated factors among teachers at Bule Hora University, Southeast Ethiopia. A cross-sectional survey design was employed to achieve the objective of the study. Using a simple random sampling technique, 220 (200 men and 20 women) teachers who were actively working at Bule Hora University during the study period were selected. Maslach Burnout Inventory (MBI), General Self-efficacy Scale (GSE), Rosenberg Self-esteem Scale (RSE), and Life Orientation Test-Revised (LOT-R) were used to collect the data. Then, quantitative data analysis techniques such as frequency, percentage, Pearson’s Product Moment correlation, and linear regression analysis were conducted to analyze the collected data. The study showed a significant positive correlation between personal accomplishment and self-efficacy (r=0.435, p<0.01), whereas optimism had a negative correlation with emotional exhaustion (r=-0.315, p<0.01) and depersonalization (r=-0.289, p<0.01). While self-efficacy significantly predicted personal accomplishment (B=0.690, t=7.107, p<0.01), optimism significantly predicted both emotional exhaustion (B=-0.143, t=-4.898, p<0.01) and depersonalization (B=-0.407, t=-4.456, p<0.01). From this result, we can conclude that the prevalence of burnout is attributed to self-efficacy and optimism. Therefore, concerned parties ought to design appropriate interventions that incorporate self-efficacy and optimism to manage university teachers' burnout.